ANALISIS METODE ON THE JOB TRAINING TERHADAP KINERJA KARYAWAN (STUDI PADA PDAM KOTA MAGELANG) - Rachman Aditya; Dian Marlina Verawati (Economos : Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted to determine the effect of on the job training method on employee performance. On the Job Training method is one of the training methods used by PDAM Magelang such as job rotation and special tasks. This research uses quantitative methods. In this research the population is the employees of PDAM Magelang City of Engineering and Customer Relations section and the number of samples taken was 90 respondents. The data analysis technique used is a simple linear regression test which aims to determine the effect of on the job training method variables on employee performance. The results of this research indicate that there is a significant effect of the on the job training method on employee performance. The t-count value of 5.126 is greater than the t-table of 1.987 at the 95% confidence level (α=5%) and DF = 90, with a significance value of 0.000 less than 0.05. So it can be interpreted that the on the job training method has a significant effect on employee performance at PDAM Magelang City. And from the findings in the field, it shows that the on the job training method helps to get the job done and provides additional knowledge.